1992
DOI: 10.1002/hed.2880140203
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric functional endonasal sinus surgery: Review of 210 cases

Abstract: Functional endonasal sinus surgery (FESS) is an effective treatment for chronic or recurrent sinusitis in children, most of whom have failed more conservative medical treatment. The endoscopes used in FESS allow direct visualization of the diseased tissue and restoration of physiologic mucociliary clearance, enabling the sinus mucosa to return to its normal condition after the procedure. For a period of 3 to 36 months, we followed the recovery of 210 children who underwent FESS between 1986 and 1989. The age r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 6 publications
3
68
0
3
Order By: Relevance
“…Participants: Consecutive 10-month sample of 41 children aged 2 to 13 years who met the following criteria: (1) roentgenographically documented sinusitis, (2) at least one 3-week course of a \g=b\-lactamase stable antibiotic, (3) 3 months or more of clinical symptoms or three or more annual recurrences, (4) Accepted for publication September 13, 1994. Presented …”
mentioning
confidence: 99%
“…Participants: Consecutive 10-month sample of 41 children aged 2 to 13 years who met the following criteria: (1) roentgenographically documented sinusitis, (2) at least one 3-week course of a \g=b\-lactamase stable antibiotic, (3) 3 months or more of clinical symptoms or three or more annual recurrences, (4) Accepted for publication September 13, 1994. Presented …”
mentioning
confidence: 99%
“…Nonetheless, in the study by Lazar et al, 15 nasal endoscopic examination and close postoperative follow-up were other prognostic factors. Stammberger stated that follow-up treatment of adult patients after FESS, consisting of cleaning crusted blood and eschar, is essential.…”
Section: Commentmentioning
confidence: 94%
“…[17][18][19] Mitchell et al 17 reported no difference in clinical outcome in their study comparing 50 children who underwent SLE after FESS with 50 children who did not undergo SLE. Lazar et al 15 reported that of 210 patients who underwent FESS, postoperative nasal endoscopic examination showed significant adhesions between the middle turbinate and the septum in only 20% of the studied group. Ten percent of patients had granulation tissue formation, 7% had persistent polyposis, and 11% had significant crusting.…”
Section: Commentmentioning
confidence: 97%
“…Other reports on the prevalence of nasal polyps in pediatric sinus surgery have ranged from 7% to 18.8% [33][34][35]. Tissue from pediatric nasal polyps might mimic an adult eosinophilic state or, less commonly, neutrophilia.…”
Section: Pediatric Crs With Polyps (Pediatric Crswnp)mentioning
confidence: 99%